G protein‐coupled estrogen receptor and estrogen receptor ligands regulate colonic motility and visceral pain. Issue 7 (12th February 2017) - Zielińska, M.; Fichna, J.; Bashashati, M.; Habibi, S.; Sibaev, A.; Timmermans, J.‐P.; Storr, M.
Abstract: Background: Diarrhea‐predominant irritable bowel syndrome (IBS‐D) is a functional gastrointestinal (GI) disorder, which occurs more frequently in women than men. The aim of our study was to determine the role of activation of classical estrogen receptors (ER) and novel membrane receptor, G protein‐coupled estrogen receptor (GPER) in human and mouse tissue and to assess the possible cross talk between these receptors in the GI tract. Methods: Immunohistochemistry was used to determine the expression of GPER in human and mouse intestines. The effect of G‐1, a GPER selective agonist, and estradiol, a non‐selective ER agonist, on muscle contractility was characterized in isolated preparations of the human and mouse colon. To characterize the effect of G‐1 and estradiol in vivo, colonic bead expulsion test was performed. G‐1 and estradiol activity on the visceral pain signaling was assessed in the mustard oil‐induced abdominal pain model. Key Results: GPER is expressed in the human colon and in the mouse colon and ileum. G‐1 and estradiol inhibited muscle contractility in vitro in human and mouse colon. G‐1 or estradiol administered intravenously at the dose of 20 mg/kg significantly prolonged the time to bead expulsion in females. Moreover, G‐1 prolonged the time to bead expulsion and inhibited GI hypermotility in both genders. The injection of G‐1 or estradiol resulted in a significant reduction in the number of pain‐induced behaviors in mice. Conclusions and Inferences: GPER and ER receptors are involved in the regulation of GI motility and visceral pain. Both may thus constitute an important pharmacological target in the IBS‐D therapy. Abstract : Estrogen receptors (ER) and G protein‐coupled estrogen receptors are involved in colonic motility and visceral pain. GPER is expressed in the human colon. G‐1, a selective GPER agonist, and estradiol, a non‐selective ER agonist, inhibited muscle contractility in vitro in human colon.